Serous Effusions Etiology, Diagnosis, Prognosis and Therapy (Springer International Publishing, 2018)
This revised and updated second edition contains multiple microscopic illustrations of all diagnostic entities and ancillary techniques, providing a comprehensive, authoritative guide to all aspects of serous effusions. It now includes the many new antibodies which have been tested since the previous edition, as well as a discussion on next-generation sequencing and molecularly targeted therapy. Section one covers diagnosis for benign and malignant effusions while section two discusses biology, therapy, and prognosis highlighting clinical approaches that may be of value. Serous Effusions provides an indispensable guide to all aspects of current practice for cytopathologists, cytotechnicians, pathologists, clinicians and researchers in training and practice.